Socio - Demographic Profile of Patients Attending in Outpatient Department in a General Hospital - An Observational Study (KYAMC Journal, 2013)
Background : Bangladesh has had tremendous development when it comes to health. With greater emphasis given to health, more and more people has become health conscious and seek medical attention early in their disease course. Our study looked at the pattern of the medicine OPD consultation in a peripheral center. Methodology: It was an observational study where all patients coming to the outpatient department of a 250 bed general hospital cum newly formed medical college were included in the study. Data was collected viewing the OPD patient registry and a short questionnaire over a three month period. Results: Over a three months period, a total of 2344 patients were seen in OPD. Among them, 1247 were male (53.19%),1097 were female(46.81%). Most of the patients belonged to the 35-54 age group(47%). Only 3%(70 patients) required admission. Among the patients seeking consultation, around 79% were actually seeking consultation, rest were looking for free medicine. Majority patients had PUD(982).630 patients had IBS. Conclusion: Over the years, there has been a shift in health awareness among Bangladeshi people which is reflected in our study.OPD need more attention for effective functioning of hospitals. KYAMC Journal Vol. 3, No.-2, January 2013, Page 294-297 DOI: http://dx.doi.org/10.3329/kyamcj.v3i2.15170